2008
DOI: 10.1002/art.23694
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of pulmonary fibrosis for twenty weeks with imatinib mesylate in a patient with mixed connective tissue disease

Abstract: Interstitial lung disease, which is common in patients with mixed connective tissue disease (MCTD), can progress to severe pulmonary fibrosis. The tyrosine kinase inhibitor imatinib mesylate has recently been shown to prevent experimental pulmonary, dermal, and renal fibrosis. Our patient, a 64‐year‐old woman with MCTD and rapidly progressive pulmonary fibrosis, presented with rapid deterioration despite treatment with immunosuppressants. During 20 weeks of treatment with imatinib mesylate at 400 mg/day, our p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 15 publications
2
27
0
1
Order By: Relevance
“…In bleomycininduced mice, PDGF was significantly increased in murine pulmonary tissues (24), and target its expression could availably prevent the progress of fibrosis. In human studies, similar results show that imatinib, which specifically inhibits PDGF tyrosine kinase (25), could obviously improve the pulmonary function in IPF patients (26). Accordingly, our study also suggests that PDGF may a potential target for pulmonary fibrosis, especially for INSIP patients since its expression was negatively associated with the survival rate of patients with INSIP in our study.…”
Section: Discussionsupporting
confidence: 83%
“…In bleomycininduced mice, PDGF was significantly increased in murine pulmonary tissues (24), and target its expression could availably prevent the progress of fibrosis. In human studies, similar results show that imatinib, which specifically inhibits PDGF tyrosine kinase (25), could obviously improve the pulmonary function in IPF patients (26). Accordingly, our study also suggests that PDGF may a potential target for pulmonary fibrosis, especially for INSIP patients since its expression was negatively associated with the survival rate of patients with INSIP in our study.…”
Section: Discussionsupporting
confidence: 83%
“…Bronchial fibroblasts from that patient obtained via bronchoalveolar lavage prior to treatment showed a decreased PDGF-induced proliferation response in a fibroblast proliferation assay, and decreased TGF-β-induced collagen Ia1 synthesis by quantitative polymerase chain reaction with in vitro exposure to imatinib. Distler et al [41] described a patient with mixed connective tissue disease with pulmonary fibrosis who demonstrated an improvement in the ground-glass opacities seen on high-resolution CT scan of the chest, as well as an improved DLCO and 6-minute walk distance with imatinib treatment. Chung et al [42•] reported similar outcomes in two patients treated with imatinib, 200 mg/d.…”
Section: Case Reports and Case Seriesmentioning
confidence: 97%
“…Imatinib was also an efficient therapy in two patients with gadolinium-induced nephrogenic systemic fibrosis (41). We reported the successful treatment of pulmonary fibrosis with imatinib in a patient with anti-U1-antibodypositive mixed connective tissue disease (42). Before initiation of imatinib, the patient deteriorated despite treatment with corticosteroids and immunosuppressives.…”
Section: Clinical Efficacy Of Imatinib In Sscmentioning
confidence: 99%